National Health Examination Survey, Cycle I, 1959-1962: Dental Findings ([Verlag nicht ermittelbar], 1989)
The National Health Examination Surveys, Cycle I (NHES I), conducted during the period 1959-1962, were designed to secure statistics on the health status of the population of the United States. More specifically, their purpose was to determine the prevalence of certain chronic diseases, the status of dental health, and the distributions of auditory and visual acuity and certain anthropometric measurements. This collection includes findings from dental examinations on the condition of individual teeth and also provides assessments of periodontal disease, oral hygiene, and malocclusion. There are also two demographic variables, one on age/sex and one on race/sex.